Key problems of seismic zoning of urban areas adjacent to the Mongolia-Siberian region (by the example of Erdenet town) - Dzhurik, VI; Dugarmaa, T; Serebrennikov, SP; Batsaikhan, Ts (Proceedings of the Mongolian Academy of Sciences, 2011)
The first approximation approach to seismic zoning of the areas adjacent to the Mongolia-Siberian region has been followed by the example of Erdenet town. The grounds have been given for problematic stages of working: study of some regular trends of seismic setting and current level of initial seismicity of the area; identification of seismic activity areas and assessment of their seismic potential; seismic modeling of sites with the most typical soil conditions; model theoretical calculating of basic parameters of seismic effects and model zoning of the investigated area. Technically, the stages of Erdenet town case study can serve as a basis for seismic zoning of the areas of interest that are adjacent to the Mongolia-Siberian region. The work has been done under financial support of RFBR project No. 07-05- 90111. DOI: http://dx.doi.org/10.5564/pmas.v0i4.38 Proceedings of the Mongolian Academy of Sciences 2007 No 4 pp.17-35